THE EFFECT OF GADGETS ON STUDENTS’ LEARNING OUTCOMES IN IT SUBJECT AT GRADE V SD ST. ANTONIUS BANGUN MULIA MEDAN - Melfa Norestina Sidebang; Rumiris Lumbangaol; Ester J Simarmata; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The results of data analysis and hypothesis testing and discussion concluded that this study aimed to find out the effect of gadgets on students’ learning outcomes in IT subject at grade V SD St Antonius Bangun Mulia Medan in the academic year 2020/2021. The population of this study was 55 students and all of the students were selected as the sample in this study. A quatitative method with survey type was utilized to obtain the data required in this study. The samples were chosen through random sampling technique. Then, the data were obtained from observations, questionnaires, and document studies. Te hypothesis was tested by using correlation test and t test. The results of this study concluded that the initial average score of the students’ learning outcome was 66.90 which was categorized as Fair with a percentage of 32.72%. After using the gadget in learning, the average score of students’ learning outcome was 85.36 which was categorized as Fair with a percentage of 34.54%. Furthermore, the result of hypothesis testing obtained rcount = -0.169 and tcount = -1248 while ttable = 1,673 at a significant level of 5%. Therefore, tcount < ttabel in which was -1248 < 1,673. Thus, H0 was accepted and Ha was rejected. This confirmed that gadgets had no effect on the students’ learning outcomes at grade V SD St. Antonius Bangun Mulia Medan.